Pengaruh Kurikulum Berbasis Nilai Karakter Dan Empati Emosional Terhadap Kepedulian Sosial Siswa di MA Annajah Bekasi - Faiqotus Silvia Nabila Nabila; Samsimah; Saepul Malik; Muhammad Alfi Syahrin (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This research was carried out to investigate the influence of a character value-based curriculum and emotional empathy on the social awareness of students at MA Annajah Bekasi. The background of this study was the decline in students’ concern for social issues due to the impact of globalisation and the rapid growth of digital technology, which have gradually changed adolescents’ patterns of communication and interaction in everyday life. The study used a quantitative approach with a correlational research design. The participants were Year 11 students at MA Annajah Bekasi, and the sample was selected through a simple random sampling method. Data were gathered using a Likert-scale questionnaire consisting of 36 statements related to the implementation of character education, emotional empathy, and students’ social awareness. The collected data were analysed through multiple linear regression analysis. The findings demonstrated that the character value-based curriculum and emotional empathy had positive and significant effects on students’ social awareness. In addition, both variables simultaneously contributed strongly to improving students’ attitudes and awareness towards their social environment. Therefore, strengthening character education and emotional empathy can be considered an effective strategy to develop students’ social responsibility and positive behaviour in school life.